Chapter Plastic pollution on the Tuscan coast: environmental measures municipalities can put in place to reduce it - Ballerini, Tosca; Galletti, Yuri; Tacconi, Daniela (Firenze University Press, 2025)
Pollution by plastics and other chemical pollutants is outside of safe operating space of the planetary boundary for humanity. Scientific evidence shows that to address plastic pollution, it is urgently needed to deploy upstream interventions to reduce Primary Plastic Polymers production. In parallel to actions at the international and national level, municipalities can significantly limit single-use plastic pollution on their territory through the development of integrated strategies. Here, we show results of beach litter monitoring on three municipalities of the Tuscan coast, Tyrrhenian Sea. We identified environmental measures put in place by the municipalities to address single-use plastic (SUP) items and highlight further possible environmental measures to reduce plastic pollution at the local level.